Analisis Pemain Terbaik Sepak Bola dengan menggunakan Algoritma K-Means - Wardhana, Faviola Proba; Winarno, Sri (Universitas Hamzanwadi, 2024)
The selection of players in soccer is crucial for developing strategies in matches. It serves as a decision support system that can be used to choose the starting line-up. The data for this research was obtained from the official and reliable website of Liga 1 Indonesia for the 2023 season. This study aims to analyze the top soccer players using the K-means algorithm based on their statistical performance throughout the 2023 Liga 1 Indonesia season. Data collection for each player included their percentage of appearances in the starting line-up. We used the K-means algorithm, which helps identify patterns and cluster players based on statistical metrics from the matches, such as the number of goals, assists, and other physical statistics across various player positions. The data comprised 197 players competing in Liga 1 2023. Our findings reveal that 62 players belong to Cluster 1 out of the total 197 analyzed. These players exhibited the best statistics and could be potential options for Liga 1 coaching staff to recruit or sign in order to strengthen their teams for the next season. Our research indicates that the players in this cluster demonstrated outstanding performance, helping coaches identify categories such as